Atomic, molecular and optical physics section: (LU FMOF Laser Centre section): Book of Abstracts, 1st of February 2024, Jelgavas street 3, Riga - 82nd International Scientific Conference of the University of Latvia; University of Latvija. Laser centre (Laser Centre, University of Latvia, 2024)
This book of abstracts is made for the Laser Centre section "Atomic, molecular and optical physics section", that occurred as a part of the 82nd International Scientific Conference of the University of Latvia. This section was organized by the staff of Laser Centre of the University of Latvia and was held on the 1st of February, 2024. The book of abstracts contains contributions from researchers working on various light-matter interaction problems from all four laboratories of the Laser Center - Atomic and Molecular Physics Laboratory, Molecule Optical Polarization Laboratory, Color centre laboratory and Laboratory of Astrospectroscopy.
Atomu, molekulu un optiskas fizikas sekcija (LU FMOF Lāzeru Centra sekcija)
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics::Atomic and molecular physics::Atomic physics; Research Subject Categories::NATURAL SCIENCES::Physics::Atomic and molecular physics::Molecular physics